A influência de capacidades dinâmicas e incertezas ambientais na propensão para a internacionalização de empresas de base tecnológica em uma economia emergente - Piveta, Maíra Nunes (2022)
The thesis is defended that dynamic capabilities and environmental uncertainties can influence the propensity for internationalization of Brazilian technology-based companies. Therefore, the objective of this study is to analyze the influence of dynamic capabilities – adaptive, absorptive and innovative – and of environmental uncertainties on the propensity for internationalization of technology-based companies (EBTs) in an emerging economy. Thus, the methodological support covers an applied and descriptive/explanatory research, the scientific method is hypothetical-deductive and exploratory, with regard to the nature of the data, it was characterized as quantitative, through a survey, having as application period the months of August 2021 to February 2022 - period marked by the Covid-19 pandemic - configuring a sample of 137 companies. Thus, a research protocol segmented into five parts was applied to the respondents: sociodemographic profile of the respondents; characterization of companies; dynamic capabilities scale (ADP; ABS; INN); environmental uncertainty scale (IAT; IAM) and international growth orientation scale (OCI). As a method of data treatment, structural equation modeling (SEM), descriptive measures and standardization of scores were used. With regard to scientific contributions, it is possible to list them according to the specific objectives proposed: a) regarding the characterization of the analyzed EBTs, most were configured as young micro-enterprises, from 1 to 5 years of existence in the market, with revenue annual average of less than R$250 thousand, mostly located in the South and Southeast regions of the country and in various sectors, especially SaaS (Web App), Agribusiness and Education. Most of the sample also stated that they were part of some type of innovation environment and did not have commercial activities abroad; b) the dynamic adaptive, absorptive and innovative capacities, the environmental uncertainties and the orientation towards international growth were described through the frequency, mean and standard deviation of their indicators; c) a research model was proposed and validated based on the literature with the analysis of seventeen hypotheses and sub hypotheses that were empirically tested resulting in the acceptance of eight hypotheses; d) there was a role of mediation of technological uncertainties in the relationship between absorptive and innovative capacities and the propensity for internationalization, since the environmental market uncertainties did not mediate any of the proposed relationships; e) the standardization of adaptive, absorptive and innovative capacity scales returned high levels indicated by 86.86% (n=119), 88.32% (n=121) and 93.43% (n=128) respectively. On the other hand, a low general level of the OCI scale was identified, indicating that 40.88% (n=56) of the companies examined are not prone to internationalization. Finally, it was concluded that the thesis initially defended was partially corroborated by verifying that only adaptive capacity and technological environmental uncertainty influence the propensity for internationalization in technology-based companies. Furthermore, it was found that only technological environmental uncertainty had a mediating effect on the proposed relationships.